2020
DOI: 10.1111/jdv.16347
|View full text |Cite
|
Sign up to set email alerts
|

The importance of proper and prompt treatment of ocular syphilis: a lesson from permanent vision loss in 52 eyes

Abstract: Background Ocular involvement can occur at any stage of syphilis. Prompt diagnosis and proper treatment of ocular syphilis are vital to avoid long‐term consequences. Objectives To describe the risk factors for ocular syphilis and clinical features of blindness caused by syphilis. Methods We report risk factors for ocular syphilis amongst patients seen at the Shanghai Skin Disease Hospital between October 2009 and October 2017. We identify pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
4

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 33 publications
2
19
0
4
Order By: Relevance
“…Eye involvement may even present as the only sign of syphilis requiring treatment [4,8]. Any part of the eye may be affected [5,9]. Syphilis was only diagnosed based on the ophthalmologic symptoms in patients 2, 3, and 4.…”
Section: Discussionmentioning
confidence: 99%
“…Eye involvement may even present as the only sign of syphilis requiring treatment [4,8]. Any part of the eye may be affected [5,9]. Syphilis was only diagnosed based on the ophthalmologic symptoms in patients 2, 3, and 4.…”
Section: Discussionmentioning
confidence: 99%
“…Neurosyphilis is a complicated and serious condition that can occur if syphilis treatment is delayed or not properly performed in the early stage. Late-stage neurosyphilis can cause permanent central nervous system damage even after proper treatment, leading to conditions such as dementia, 11 blindness, 12 hearing loss, 13 and paralysis. 14 In HIV/syphilis co-infected patients, it is extremely important to promptly diagnose neurosyphilis, especially in the asymptomatic stage.…”
Section: Discussionmentioning
confidence: 99%
“…Dhungana et al [12] reported that syphilis can progress to syphilitic optic neuropathy if left untreated as evidenced by poor vision and RAPD in our patient. A study by Gu et al [13] showed that delayed treatment for syphilitic optic neuropathy can lead to significant permanent visual loss. Hence, all patients with optic neuritis should be tested for syphilis by definitive investigations.…”
Section: Discussionmentioning
confidence: 99%